Paper protective agent with reinforcing, antibacterial, mildew-proof and ultraviolet aging-proof functions and application
Through the multifunctional protective agent combined with nanocellulose and N-doped carbon quantum dots, the problems of paper cultural relics enhancement, antibacterial and mildew protection and ultraviolet aging in the prior art are solved, and a comprehensive protection effect of green and safe is achieved , reduces the harm to paper cultural relics and improves their strength and durability.
Patent Information
- Application Number
- CN202411572560.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The prior art is carried out in the enhancement of paper cultural relics, antibacterial and mildew protection and ultraviolet aging, which leads to increased costs, environmental hazards and damage to paper cultural relics, and the use of chemical agents increases the harm to cultural relics.
Using a multifunctional protective agent made of nanocellulose and N-doped carbon quantum dots, nanocellulose is prepared by peracetic acid method to retain hemicellulose. N-doped carbon quantum dots are derived from apigenin and 3-ammonia. Propyltriethoxysilane, used for enhancement, antibacterial, mildew and anti-ultraviolet aging.
It achieves green and safe paper enhancement, antibacterial and mildew resistance and UV aging, reduces the damage caused by multiple drug use to paper cultural relics, improves the strength and durability of paper, and significantly inhibits the growth of mold and bacteria.
Smart Images

Figure CN119308176A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of paper protection, and in particular relates to a paper protective agent with enhancement, antibacterial and mildew-proof and anti-ultraviolet aging functions and its application. Background Art
[0002] Paper artifacts, as carriers of civilization, record the rise and fall of a country and have immeasurable historical value. my country has conducted in-depth research on the preservation of paper artifacts. However, due to many adverse effects such as intentional damage, production methods, and microbial contamination, these paper artifacts have long been severely acidified, aged, yellowed, and brittle, and some documents have even become powdered. Many paper artifacts have suffered irreparable losses due to microbial erosion, so the enhancement, antibacterial and anti-mildew, and anti-aging of aged paper have become important research directions for many researchers.
[0003] After paper breeds microorganisms, their metabolic waste will reduce the pH value of the paper, accelerate paper aging, and eventually turn the paper yellow and brittle. The extracellular enzymes secreted by molds will degrade organic substances such as cellulose, which not only destroys the structure of the paper, but also reduces the mechanical properties of the paper, and even makes the paper stick together and cannot be read. In addition, the colored pigments secreted by these molds will leave mold spots on the paper, seriously damaging the original appearance of the cultural relics, not only covering the ink marks on the paper cultural relics, but also affecting the viewing effect. If it is difficult to completely remove it, the cultural relics will lose their due precious value. Moreover, the products of molds are mostly organic acids, which will further reduce the mechanical properties of the paper, turn it yellow, and become brittle. Therefore, antibacterial and anti-mildew protection of paper cultural relics is particularly important.
[0004] At present, the antibacterial treatment of paper can be divided into two aspects: the antibacterial treatment of paper itself and the antibacterial treatment of storage space. Among them, chemical fumigation is the most widely used method for antibacterial treatment of paper, such as the use of chemical reagents such as polyoxymethylene and phosphine. However, the toxicity of such reagents can seriously harm the skin and respiratory system of archive managers and readers.
[0005] Polymers used for reinforcement include polyvinyl acetate, polyacrylic acid, polyvinyl alcohol, etc., but synthetic materials have problems such as poor polymer stability and poor compatibility with paper fibers. Some natural polymers have also been used for paper reinforcement, such as gelatin, chitosan, and cellulose. Among them, nanocellulose has become one of the most promising and widely studied solutions for paper reinforcement due to its optical transparency, high specific surface area, high crystallinity, high strength, degradability, and colloidal dispersion stability.
[0006] In the prior art, the enhancement, antibacterial and mildew-proofing, and anti-ultraviolet aging of paper cultural relics are mostly carried out separately. The increase of reagents and operating procedures not only increases the cost, but also causes harm to the surrounding environment. More importantly, with the increase in the use of chemical agents, the harm to paper cultural relics also increases. Summary of the invention
[0007] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a green, natural, safe, multifunctional protective agent that can enhance paper cultural relics, and has antibacterial, mildew-proof and UV-proof effects. The multifunctional protective agent is composed of nanocellulose and N-doped carbon quantum dots. Nanocellulose plays a role in enhancing and reinforcing paper, and the N-doped carbon quantum dots have the functions of antibacterial, mildew-proof and UV-proof. In the present invention, nanocellulose is prepared by the peracetic acid method, which retains most of the hemicellulose and has a low carboxyl content, which helps to improve the enhancement effect of paper; the N-doped carbon quantum dots in the protective agent have a carbon source derived from apigenin and a N source derived from 3-aminopropyltriethoxysilane, and the N-doped carbon quantum dots have excellent antibacterial and mildew-proof effects.
[0008] The method for preparing nanocellulose provided by the present invention comprises the following steps:
[0009] (1) Cut 5 g of the original pulp board into pieces, place them in a beaker, add 800 mL of 0.1 M hydrochloric acid solution and soak for 24 h, then use a household wall-breaking machine to grind the pulp, and filter;
[0010] (2) adding 1 g of the filtered pulp with an absolute dry weight into 50 mL of 4 wt% peracetic acid solution and treating with a homogenizer at 16,000 rpm for 5 min;
[0011] (3) After adjusting the solution pH to 4.8, the pulp was added to a three-necked bottle and reacted at 85° C. for 45 minutes. After filtering, 4 wt % peracetic acid solution was added again. This step was repeated 4 times and the pulp was washed with deionized water until the pH was neutral; nanocellulose was obtained by treating with a high-pressure homogenizer (500 bar) for 30 minutes.
[0012] The preparation method of N-doped carbon quantum dots provided by the present invention is as follows: 30 mg of apigenin and 2-5 mL of 3-aminopropyltriethoxysilane (the molar ratio of apigenin to 3-aminopropyltriethoxysilane is 1:80-200) are added to 30 mL of ethanol to dissolve, and then transferred to a 50 mL high-pressure reactor, reacted at 210° C. for 10 hours, and after the reaction, filtered through a 0.22 μM microporous membrane to obtain an N-doped carbon quantum dot dispersion.
[0013] The protective agent of the present invention is used for strengthening aged paper, resisting bacteria and mildew, and preventing ultraviolet aging. The specific application method is: preparing nanocellulose and N-doped carbon quantum dots into an isopropanol suspension, coating the protective agent suspension on 26cm×18cm paper in batches with a glass rod, and then placing the paper in a vacuum drying oven for vacuum drying at 30°C, wherein the amount of nanocellulose used is 0.1-1mg / cm 2 Paper, the amount of N-doped carbon quantum dots is 1-4 mg / cm 2 Paper.
[0014] The isopropanol solution is an isopropanol aqueous solution with a volume ratio of 80 / 20.
[0015] GB / T 47-1989 was used to determine the lignin content of the prepared nanocellulose.
[0016] The hemicellulose content of the prepared nanocellulose was determined using GB / T 2677.9-1994.
[0017] The treated aged paper was placed in a constant temperature and humidity environment (23±1°C, 50±2%RH) for 24 hours, and the tensile strength, folding endurance and tear resistance of the aged paper before and after treatment were measured using GB / T 12914-2018, GB / T 457-2008 and GB / T 455-2002 respectively.
[0018] The above-mentioned paper deacidification, antibacterial and anti-mildew and anti-ultraviolet aging protective agent is used. The aged paper used is the "Popular Movies" magazine paper published in 1980, and its basis weight is 53.0±1.0g / m 2 , pH is 4.6-4.7.
[0019] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0020] (1) The nanocellulose prepared by the peracetic acid method in the protective agent removes lignin while retaining most of the hemicellulose. The retention of hemicellulose improves the strength of paper to a certain extent.
[0021] (2) The N-doped carbon quantum dots synthesized in the protective agent can play a significant antibacterial and anti-mildew effect when applied to paper, and the application of N-doped carbon quantum dots can make the paper have a certain ability to resist ultraviolet aging.
[0022] (3) The protective agent has the functions of paper strengthening, antibacterial and anti-mildew, and anti-ultraviolet aging. It is not only green and safe, but also reduces the damage to paper cultural relics caused by repeated use of drugs. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The fluorescence emission spectrum of the N-doped carbon quantum dots prepared in Example 1 (in the figure, EX represents the excitation wavelength);
[0024] Figure 2 TEM image of nanocellulose prepared in Example 1;
[0025] Figure 3 The effect of nanocellulose dosage on the folding endurance of paper samples before and after dry heat aging;
[0026] Figure 4The effect of nanocellulose dosage on the tearing strength of paper samples before and after dry heat aging;
[0027] Figure 5 The effect of nanocellulose dosage on the tensile strength of paper samples before and after dry heat aging;
[0028] Figure 6 The effect of N-CQDs dosage on the folding endurance of paper samples before and after UV aging;
[0029] Figure 7 The effect of N-CQDs dosage on the tearing strength of paper samples before and after UV aging;
[0030] Figure 8 The effect of N-CQDs dosage on the tensile strength of paper samples before and after UV aging;
[0031] Fig. 9 The inhibitory effect of N-CQDs on Aspergillus niger after acting on paper samples;
[0032] Fig.10 The inhibitory effect of N-CQDs on Staphylococcus aureus after acting on paper samples;
[0033] Fig.11 The inhibitory effect of N-CQDs on Escherichia coli after acting on paper samples;
[0034] Fig.12 This is the inhibitory effect of CQDs on Aspergillus niger after acting on the paper sample in Comparative Example 1. DETAILED DESCRIPTION
[0035] The present invention will be further described in detail below in conjunction with specific examples. These examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention in any way.
[0036] Example 1
[0037] The original pulp board with an absolute dry mass of 5g was cut into pieces, placed in a beaker, added with 800mL of 0.1M hydrochloric acid solution and soaked for 24h, and then crushed with a household wall breaking machine to obtain pulp; the pulp with an absolute dry mass of 1g after filtration was added to 50mL of 4wt% peracetic acid solution, and treated with a homogenizer at 16000rpm for 5min; after adjusting the pH to 4.8, the pulp was added to a three-necked bottle and reacted at 85°C for 45min, then filtered and 4wt% peracetic acid was added again, the above steps were repeated 4 times, and the pulp was washed with deionized water until the pH was neutral, and then treated with a high-pressure homogenizer (500bar) for 30min to obtain nanocellulose. The test results of hemicellulose and lignin in the prepared nanocellulose are shown in Table 1 below:
[0038] Table 1
[0039] Lignin Hemicellulose Original pulp (%) 3.45 16.28 Nanocellulose (%) 0.6 8.28
[0040] 30 mg of apigenin and 3 mL of 3-aminopropyltriethoxysilane were added to 30 mL of ethanol for dissolution, and then transferred to a 50 mL high pressure reactor and reacted at 210° C. for 10 h. After the reaction, the N-doped carbon quantum dot dispersion was obtained by filtration through a 0.22 μM microporous membrane.
[0041] The nanocellulose and N-doped carbon quantum dots were added to an isopropanol aqueous solution with a volume ratio of 80 / 20 to prepare a 20 mL suspension, which was coated on aged paper of about 26 cm × 18 cm in portions using a glass rod. The treated paper samples were placed in a vacuum drying oven and vacuum dried at 30 °C. The amount of nanocellulose used was 0.6 mg / cm 2 Paper, the amount of N-doped carbon quantum dots is 0.5 mg / cm 2 Paper.
[0042] The paper used in the experiment was the paper of "Popular Movies" magazine published in 1981. After the dried paper samples were placed in an environment of 23±1℃ and 50±2%RH for 24 hours, the tensile index, tear strength, folding endurance, color difference and whiteness (before aging) of the treated paper samples were measured. At the same time, some of the paper samples that had been placed in an environment of 105℃±2℃ for 72 hours of dry heat aging and 340nm ultraviolet light irradiation for 72 hours were tested for the relevant properties of the paper (after aging).
[0043] Example 2
[0044] 30mg of apigenin and 2mL and 5mL of 3-aminopropyltriethoxysilane were added to 30mL of ethanol to dissolve, and then transferred to a 50mL high-pressure reactor, reacted at 210℃ for 10h, and filtered through a 0.22μM microporous membrane to obtain a N-doped carbon quantum dot dispersion. The N-doped carbon quantum dot stock solution was characterized using a fluorescence spectrophotometer, and it was found that when 2mL of 3-aminopropyltriethoxysilane (providing an alkaline environment) was added, apigenin could not be completely dissolved, and the obtained N-carbon quantum dots had no fluorescence; when 5mL of 3-aminopropyltriethoxysilane was added, the fluorescence intensity of the obtained N-doped carbon quantum dot stock solution was significantly weakened.
[0045] Example 3
[0046] The nanocellulose and N-doped carbon quantum dots prepared in Example 1 were added to an isopropanol aqueous solution with a volume ratio of 80 / 20 to prepare a 20 mL suspension, which was coated on aged paper of about 26 cm × 18 cm in portions using a glass rod, and then placed in a vacuum drying oven and vacuum dried at 30 ° C. The amounts of nanocellulose used were 0.1, 0.2, and 1 mg / cm 2 Paper, the amount of N-doped carbon quantum dots on the paper sample was fixed at 0.5 mg / cm 2Paper. After drying, the paper samples were placed in an environment of 23±1℃, 50±2%RH for 24 hours, and the tensile index, tear strength, folding endurance, color difference and whiteness (before dry heat aging) of the treated paper samples were measured. At the same time, some of the paper samples that had been placed in an environment of 105℃±2℃ for 72 hours of dry heat aging were tested for the relevant properties of the paper samples (after dry heat aging).
[0047] The fixed N-CQD dosage is 0.5 mg / cm 2 Paper, changing the amount of nanocellulose (CNF), the test results of paper sample whiteness and color difference performance are shown in Table 2:
[0048] Table 2
[0049]
[0050] Example 4
[0051] The nanocellulose and N-doped carbon quantum dots prepared in Example 1 were added to an isopropanol aqueous solution with a volume ratio of 80 / 20 to prepare a 20 mL suspension, which was then coated with a glass rod at a depth of about 480 cm 2 The aged paper (26 cm × 18 cm) was placed in a vacuum drying oven and vacuum dried at 30°C. The amount of nanocellulose was fixed at 0.6 mg / cm 2 Paper, the dosage of N-doped carbon quantum dots on paper was 0.25, 1, and 2 mg / cm 2 After the dried paper samples were placed at 23±1℃, 50±2%RH for 24h, the tensile index, tear strength, folding resistance, color difference and whiteness (before aging) of the treated paper were measured. At the same time, some of the paper samples after 24h were exposed to 340nm ultraviolet light for 72h. Then the tensile index, tear strength, folding resistance, color difference and whiteness (after ultraviolet aging) of the paper samples before and after ultraviolet aging were measured. The fixed nanocellulose dosage was 0.6mg / cm 2 Paper, changing the amount of N-CQD, the whiteness and color difference performance test results of the paper sample are shown in Table 3:
[0052] Table 3
[0053]
[0054] Example 5
[0055] The nanocellulose and N-doped carbon quantum dots prepared in Example 1 were added to an isopropanol aqueous solution with a volume ratio of 80 / 20 to prepare a 20 mL suspension, which was then coated with a glass rod at a depth of about 480 cm 2 The aged paper (26 cm × 18 cm) was placed in a vacuum drying oven and vacuum dried at 30°C. The amount of nanocellulose was fixed at 0.6 mg / cm 2The dosage of N-doped carbon quantum dots on paper was 0.5, 1, 2 and 4 mg / cm 2 The dried paper samples were used to measure the antibacterial and antifungal effects against Escherichia coli, Staphylococcus aureus and Aspergillus niger.
[0056] Comparative Example 1
[0057] 30 mg of apigenin was added into 30 mL of ethanol to dissolve, and then transferred into a 50 mL high pressure reactor and reacted at 210° C. for 10 h. After the reaction, the carbon quantum dot dispersion was obtained by filtering through a 0.22 μM microporous membrane.
[0058] The nanocellulose and carbon quantum dots obtained in Example 1 were added to an isopropanol aqueous solution with a volume ratio of 80 / 20 to prepare a 20 mL suspension, wherein the amount of nanocellulose was fixed at 0.6 mg / cm 2 Paper, the amount of carbon quantum dots on the paper was 0.5, 1, 2 and 4 mg / cm 2 The coating is applied on paper by a coating method and placed in a vacuum drying oven to dry under vacuum at 30°C.
[0059] Antibacterial experiments were conducted on paper coated with carbon quantum dots and nanocellulose, and it was found that the paper had no obvious inhibitory effect on Aspergillus niger.
[0060] Comparative Example 2
[0061] The original cardboard with an absolute dry mass of 5g was cut into pieces, placed in a beaker, added with 800mL of 0.1M hydrochloric acid solution, soaked for 24h, and then crushed with a household wall breaking machine to obtain pulp for use; the pulp with an absolute dry mass of 1g was added with 50mL of 8M hydrochloric acid solution, and treated with a homogenizer at 16000rpm for 5min; added to a three-necked flask under mechanical stirring conditions (speed of 600rpm), and refluxed at 110°C for 4h; after the reaction was completed, centrifuged at 6000r / min for 6min, the supernatant was removed, the precipitate was dispersed with deionized water, placed in a dialysis bag with a molecular weight cutoff of 12000-14000, and dialyzed with deionized water to neutrality; the dialyzed nanocellulose dispersion was taken out from the dialysis bag, treated with a cell crusher in an ice bath for 30min to make it evenly dispersed, and a nanocellulose dispersion was obtained.
[0062] By comparing the tensile strength of the two nanocellulose coated papers, it was found that the nanocellulose prepared by the 4wt% peracetic acid method in Example 1 enhanced the tensile strength of the paper by 34.5%, while the nanocellulose prepared by the 8M hydrochloric acid solution acid degradation method in Comparative Example 2 enhanced the tensile strength of the paper by 26.2%.
Claims
1. A paper protective agent with enhancement, antibacterial, anti-mildew and anti-ultraviolet aging functions, characterized in that: The paper protective agent consists of nanocellulose and N-doped carbon quantum dots; wherein the mass ratio of the nanocellulose to the N-doped carbon quantum dots is 0.1-1:0.5-4.
2. The paper protective agent with enhancement, antibacterial, anti-mildew and anti-ultraviolet aging functions according to claim 1, characterized in that: The preparation method of the nanocellulose is as follows: (1) Cut 5 g of the original pulp board into pieces, place them in a beaker, add 800 mL of 0.1 M hydrochloric acid solution, soak for 24 h, and then use a household wall-breaking machine to grind the pulp, which is then filtered; (2) adding peracetic acid solution to the filtered pulp and treating it with a homogenizer at 16000 rpm for 5 min; After adjusting the pH to 4.8, the pulp was added into a three-necked bottle and reacted at 85°C for 45 min, and filtered; (3) After filtering, the peracetic acid solution is added back into the pulp, and the above step (2) is repeated 4 times. The pulp is then washed with deionized water until the pH value is neutral, and treated with a high-pressure homogenizer for 30 minutes to obtain nanocellulose.
3. The paper protective agent with enhancement, antibacterial, anti-mildew and anti-ultraviolet aging functions according to claim 2, characterized in that: The mass fraction of the peracetic acid solution was 4%, the solid-liquid ratio of the dry weight of pulp to 4wt% peracetic acid was 1:50, and the pressure of the high-pressure homogenizer was 500 bar.
4. The paper protective agent with enhancement, antibacterial, anti-mildew and anti-ultraviolet aging functions according to claim 1, characterized in that: The preparation method of the N-doped carbon quantum dots is as follows: apigenin and 3-aminopropyltriethoxysilane are added to ethanol, and after dissolving, they are transferred to a 50 mL high-pressure reactor, subjected to solvent thermal reaction at 210° C. for 10 h, and filtered through a 0.22 μM microporous membrane to obtain an N-doped carbon quantum dot dispersion.
5. The paper protective agent with enhancement, antibacterial, anti-mildew and anti-ultraviolet aging functions according to claim 4, characterized in that: The molar ratio of apigenin to 3-aminopropyltriethoxysilane is 1:80-200.
6. An application of a paper protective agent having enhancement, antibacterial, anti-mildew and anti-ultraviolet aging functions according to any one of claims 1 to 5, characterized in that: The paper protective agent is used for strengthening aged paper, resisting bacteria and mildew, and preventing ultraviolet aging.
7. The use of the paper protective agent with enhancement, antibacterial, anti-mildew and anti-ultraviolet aging functions according to claim 6, characterized in that: The application method is as follows: preparing nanocellulose and N-doped carbon quantum dots into an isopropanol suspension, coating the suspension on 26 cm×18 cm paper in batches using a glass rod, and then placing the paper in a vacuum drying oven for vacuum drying at 30°C.
8. The use of the paper protective agent with enhancement, antibacterial, anti-mildew and anti-ultraviolet aging functions according to claim 7, characterized in that: The isopropanol solution is an isopropanol aqueous solution with a volume ratio of 80 / 20.
9. The use of the paper protective agent with enhancement, antibacterial, anti-mildew and anti-ultraviolet aging functions according to claim 7, characterized in that: The dosage of nanocellulose is 0.1-1 mg / cm 2 Paper, the dosage of N-doped carbon quantum dots is 0.5-4 mg / cm 2 Paper.
Citation Information
Patent Citations
Method of producing holocellulose and paper strength agent, process for the production of paper, the paper produced and use of the produced paper
CA3120959A1
Protective agent for aged paper sheet and protection method of aged paper sheet
CN108252155A
Carbon dot-magnesium hydroxide composite paper deacidification agent as well as preparation method and application thereof
CN115748295A
Multifunctional nanocellulose composite solution as well as preparation method and application thereof
CN115819848A
Composite multifunctional paper protective agent as well as preparation method and application thereof
CN116163153A